2016
DOI: 10.1080/19420889.2016.1139252
|View full text |Cite
|
Sign up to set email alerts
|

Smaug variants in neural and non-neuronal cells

Abstract: Mammalian Smaug1/Samd4a is an mRNA regulator involved in synapse plasticity and additional non-neuronal functions. Here we analyzed the expression of Smaug1/Samd4a variants and Smaug2/Samd4b in primary hippocampal neurons and non-neuronal cell lines. We found that multiple Smaug proteins are present in several mammalian cell lines, including a canonical full length Smaug1, a Smaug1 variant that lacks the third exon, termed ΔEIII, and Smaug2, the product of a highly homologous gene. These three major isoforms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…Smaug orthologs are expressed in several mammalian cell lines (Fernandez-Alvarez et al, 2016) and as expected, we found that Smaug1 forms cytosolic puncta in U2OS cells (Figure 1A). Smaug1-bodies were present is most cells (70-80%, 5 independent experiments, N≥200 cells each) with highly variable numbers.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Smaug orthologs are expressed in several mammalian cell lines (Fernandez-Alvarez et al, 2016) and as expected, we found that Smaug1 forms cytosolic puncta in U2OS cells (Figure 1A). Smaug1-bodies were present is most cells (70-80%, 5 independent experiments, N≥200 cells each) with highly variable numbers.…”
Section: Resultssupporting
confidence: 86%
“…Additionally, a construct that lacks the first 53 amino acids and termed ΔSSR1 was not able to form cytosolic bodies (Figure 5C-D). Finally, the splicing variant ΔEIII also formed cytosolic bodies (Figure 5C-D) as reported before (Fernandez-Alvarez et al, 2016).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations